Selection parameters for the improvement of seed yield and attributes in cowpea (Vigna unguiculata L. Walp.) - M. Gnanasekaran1*, P. Shanthi2, M.Gunasekaran3, K.Thiyagu4 and A.Yuvaraja4 (Electronic Journal of Plant Breeding, 2024)
The present investigation was carried out with 53 genotypes of cowpea to study association among yield contributing traits. The genotypes were sown in a randomized block design replicated with three replications at the National Pulse Research Centre, TNAU , Vamban, Pudukkottai, during Kharif,2022. Observations on ten traits were recorded and subjected to statistical analysis. The coefficient of phenotypic differences was substantially greater than the genotypic variation for all the characters under study, showing that the prevailing variation is mainly governed by the genotypic factor and substantial environmental factors. High heritability and genetic advance as percentage of mean were observed for the traits seed yield and 100 seed weight. This showed the role of additive gene action in the inheritance of these traits which gives the best chance of their improvement through simple selection. Association analysis revealed that number of cluster/plant and number of pods/plant had a significant and positive correlation on seed yield. Yield component traits viz., plant height, number of branches/plant, number of pods/cluster, number of pods/plant, 100 seed weight and seed yield were high inter-correlated among themselves. Furthermore, it was observed that the number of pods/plant, pod length, and 100 seed weight had the maximum positive direct effects on seed yield. So direct selection for these three traits could help to improve the seed yield potential of cowpea.